The Effect of Age and Gender on the Pain Scale of LBP Patients - Aulia, Nurlisa Naila; Syifak, Shobihatus; Amsori, Anabela Amoret; Ramadhana, Ain Darojah Siddiq (Jurnal Medis Islam Internasional, 2025)
Introduction: Low back pain (LBP) is a prevalent condition affecting people across various age groups and genders. Age-related degeneration and gender-specific hormonal factors are believed to influence pain perception in LBP patients. Objective: This study aims to examine the influence of age and gender on pain intensity in patients with LBP. Methods: A cross-sectional observational study was conducted on 47 patients diagnosed with LBP at RSI Jemursari Surabaya. Pain was assessed using the Numeric Rating Scale (NRS). Respondents were grouped by age (20–30, 31–40, 41–50, 51–60, >60 years) and gender (male, female). Pearson correlation and independent t-tests were used for statistical analysis. Results: Among the respondents, 89.4% were female, with the largest age group being 41–50 years (42.6%). There was a significant positive correlation between age and pain scale (r = 0.42, p = 0.003). Females reported significantly higher pain scores compared to males (p = 0.018). Conclusions: Age and gender are significantly associated with pain severity in LBP patients. Older individuals and females tend to report more intense pain. These findings highlight the importance of personalized pain management strategies considering demographic factors.